Growing outflows of technology-driven foreign direct investment from emerging economies and the implications for the international investment regime - Eva Dantas; Niclas Meyer; Thomas Stehnken (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
Drawing on expert interviews and secondary sources, this paper examines the implications of increasing outflows of technology-driven foreign direct investment (FDI) from emerging economies for the international investment regime. We focus on this issue from two angles: i) the possible changes in the international investment re-gime that are being driven by industrialised host countries as a reaction to increasing incoming FDI from emerging economies; and ii) the possible shifts in emerging econo-mies' policy stance on the international investment regime as a result of their growing role as home countries of FDI and the increasing clout of emerging multinationals. In relation to both angles we look at the specific implications for the international rules governing investment of growing outflows of FDI from emerging economies that are technology-driven. Our analysis of the existing evidence suggests that the growing flows of FDI and TFDI from emerging economies may be triggering changes in policy stances of both industrialized host countries and emerging home countries as regards international investment rules. This raises a number of interesting research questions to be further examined.
urn:nbn:de:0011-n-2791707
Keywords: 330